An LMI Approach to Stability for Linear Time-Varying System with Nonlinear Perturbation on Time Scales - Kanit Mukdasai; Piyapong Niamsup (Abstract and Applied Analysis)
We consider Lyapunov stability theory of linear time-varying system and derive sufficient conditions for uniform stability, uniform exponential stability, 𝜓-uniform stability, and h-stability for linear time-varying system with nonlinear perturbation on time scales. We construct appropriate Lyapunov functions and derive several stability conditions. Numerical examples are presented to illustrate the effectiveness of the theoretical results.